Pengembangan Platform Posyandu Terpadu Sebagai Sarana Edukasi Stunting di Desa Rancatungku - Rennyta Yusiana; Rizza Indah Mega Mandasari; Retno Setyorini; Agus Maolana Hidayat; Nadya Novandriani Karina Moeliono; Pramitha Aulia; Devie Ryana Suchendra; Robbi Hendriyanto; Arry Widodo (Literasi: Jurnal Pengabdian Masyarakat dan Inovasi, 2022)
The prevalence rate of stunting in Indonesia has now reached 27.7%, of which 1 in 3 children are stunted. This makes Indonesia the 4th country with the highest number of stunting in the world. The role of health care workers is very important in detecting early stunting in children. Health services for monitoring in the city of Bandung, especially in Rancatungku Village are commonly called Posyandu. Posyandu in Rancatungku Village has problems including in administering children's growth and development data is still done manually, which means that parents are still monitoring children's growth and development manually using a book called the Card Book Towards Health (KMS). This is considered ineffective and efficient, because there is a lot of data loss, the KMS Book is damaged, and the writing in the KMS book cannot be read which results in stunting detection in children being hampered. They need solutions to monitor the progress of child development digitally, including increasing awareness in parents to prevent and recover stunted children by providing parenting education articles online. Digital stunting monitoring and education solutions are expected to improve the performance of local health workers in detecting early stunting in children, so that Rancatungku Village can participate in helping to reduce stunting rates in Indonesia.